Prevalence of overweight, obesity and underweight in Western Australian school-aged children; 2008 compared with 2003 - Martin, K.; Rosenberg, M.; Pratt, Steve; Miller, M.; Mccormack, G.; Giles-Corti, B.; Magarey, A.; Bull, F.; Devine, A. (Cambridge University Press, 2013)
Objective: Due to rising rates of obesity globally, the present study aimed to examine differences in overweight and underweight prevalence in Western Australian schoolchildren in 2008 compared with 2003. Design: Cross-sectional study at two time points; using two-stage stratified sampling, primary and secondary schools in both metropolitan and non-metropolitan Western Australia; sample selected was representative of the State's population figures. Settings: Seventeen primary and thirteen secondary (2008) and nineteen primary and seventeen secondary (2003) schools. Government and non-government funded schools in metropolitan and non-metropolitan (regional/rural) Western Australia were recruited. Subjects: Height and weight were measured for 1708 (961 primary and 747 secondary) students in 2008 and 1694 (876 primary and 817 secondary) students in 2003. Results: Overweight and obesity prevalence in primary students was similar in 2008 (22·9 %) to 2003 (23·2 %; P > 0·05). In secondary girls overweight and obesity prevalence dropped from 23·1 % (2003) to 15·9 % (2008; P = 0·002). Secondary boys showed a slight decrease in overweight and obesity prevalence; however, this was not statistically significant (P = 0·102). Higher proportions of underweight in primary girls were observed in 2008 (9·9 %) compared with 2003 (4·2 %; P < 0·001) and in secondary girls in 2008 (9·4 %) compared with 2003 (5·5 %; P < 0·001). Conclusions: Prevalence of overweight and obesity in Western Australian primary students was stable; however, it declined in secondary students. Both primary and secondary girls showed an increase in underweight prevalence. Public health interventions are needed for the high percentage of youth still overweight, whereas the observed increase in underweight girls warrants attention and further investigation.